Contemporary use of antimicrobial prophylaxis for surgical patients: An observational cohort study. Issue 6 (3rd June 2022) - Dias, Priyanthi; Patel, Akshaykumar; Rook, William; Edwards, Mark R.; Pearse, Rupert M.; Abbott, Tom E.F.
Abstract : BACKGROUND: Antimicrobial prophylaxis is commonly used to prevent surgical site infection (SSI), despite concerns of overuse leading to antimicrobial resistance. However, it is unclear how often antimicrobials are used and whether guidelines are followed. OBJECTIVES: To describe contemporary clinical practice for antimicrobial prophylaxis including guideline compliance, the rate of postoperative infection and associated side effects. DESIGN: A prospective, multicentre, observational cohort study. SETTING: Twelve United Kingdom National Health Service hospitals. PARTICIPANTS: One thousand one hundred and sixteen patients, aged at least 18 years undergoing specific colo-rectal, obstetric, gynaecological, urological or orthopaedic surgical procedures. EXPOSURE: Compliance with guidelines for antimicrobial prophylaxis. OUTCOMES: The primary outcome was SSI within 30 days after surgery. Secondary outcomes were number of doses of antimicrobials for prophylaxis and to treat infection, incidence of antimicrobial-related side effects and mortality within 30 days after surgery. Data are presented as number with percentage (%) or median with interquartile range [IQR]. Results of logistic regression analyses are presented as odds ratio/rate ratio (OR/RR) with 95% confidence intervals (95% CIs). RESULTS: 1102 out of 1106 (99.6%) patients received antimicrobial prophylaxis, which was compliant with local guidelines in 929 out of 1102 (84.3%) cases. 2169 out of 51 28 (42.3%) doses of antimicrobials were administered as prophylaxis (median 1 [1 to 2] dose) and 2959 out of 5128 (57.7%) were administered to treat an infection (median 21 [11 to 28] doses). 56 patients (5.2%) developed SSI. Antimicrobial prophylaxis administered according to local guidelines was not associated with a lower incidence of SSI compared with administration outside guidelines [OR 0.90 (0.35 to 2.29); P = 0.823]. 23 out of 1072 (2.2%) patients experienced a side effect of antimicrobial therapy. 7 out of 1082 (0.6%) patients died. The median hospital stay was 3 [1 to 5] days. CONCLUSION: Antimicrobial prophylaxis was administered for almost all the surgical procedures under investigation. However, this was not always compliant with guidelines. Further research is required to determine whether the amount of prophylactic antimicrobials could be safely and effectively reduced without increasing the incidence of SSI.